2017
DOI: 10.3389/fphar.2017.00800
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Hypersensitivity to Carboplatin in Patients with Gynecologic Malignancies

Abstract: We evaluated the prevalence of and risk factors for hypersensitivity reactions related to carboplatin, which is commonly used to treat gynecological malignancies. All women with pathologically documented ovarian, fallopian tube, or primary peritoneal cancer treated with carboplatin alone or a carboplatin-based combination chemotherapy regimen at a single hospital between January 2006 and December 2013 were retrospectively recruited. We analyzed the incidence, characteristics, risk factors, management, and outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…The risk factors for drug anaphylaxis are previous cardiovascular morbidity and older age, with BLs, anaesthetic agents and radiocontrast media (RCM) being the most common triggers . Regarding chemotherapeutic agents, data have shown that disease severity, histological type, malignant ascites, past drug allergies and cumulative dose can induce an earlier onset and be a risk of hypersensitivity reaction development …”
Section: Risk Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…The risk factors for drug anaphylaxis are previous cardiovascular morbidity and older age, with BLs, anaesthetic agents and radiocontrast media (RCM) being the most common triggers . Regarding chemotherapeutic agents, data have shown that disease severity, histological type, malignant ascites, past drug allergies and cumulative dose can induce an earlier onset and be a risk of hypersensitivity reaction development …”
Section: Risk Factorsmentioning
confidence: 99%
“…In chemotherapy agents, essays to extend the infusion rates from one to two hours have been done to decrease the frequency of reactions with discrepant results …”
Section: Novel Tools For Managing Dhrmentioning
confidence: 99%
See 3 more Smart Citations